Structural Relationship of Factors Affecting the Performance of Oil & Gas Company: Case Study of Adnoc - Al Mansoori, Fatima Taher; Abdul Rahman, Ismail; Kasim, Rozilah (International Journal of Sustainable Construction Engineering and Technology, 2020)
This paper presents the development and analysis of Structural Equation Model (SEM) on factors affecting the performance oil & gas company. The model was constructed based on the model framework where it involved 5 groups of independent factors affecting the performance of oil & gas company and one group of dependent of the performance. Data collected from the 100 respondents of questionnaire survey among employees of the company were used in the model development. Assessments at measurement level of the model found that for the 5 most important groups of factors affecting oil & gas company are effective support system (J-group), empowerment (L-group), supporting employees (M-group), creativity and innovation (C-group), and training regularly (T-group). Assessment at structural level involved omitting one group for each iteration to evaluate the effect size and also involved bootstrapping process. It was found the model has achieved the overall model of fit known as GoF with the value of 0.436 indicating large validating power. Hopefully the study contributed either directly or indirectly to the academic and practitioners related to oil & gas industry.